2009
DOI: 10.1149/1.3118957
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Atom-Probe Tomographic Studies of Nickel Monosilicide/Silicon Interfaces on a Subnanometer Scale

Abstract: Three-dimensional atom-probe tomography was utilized to study the distribution of M (M = Pt or Pd) after silicidation of a solidsolution Ni 0.95 M 0.05 thin-film on Si(100). Both Pt and Pd segregate at the (Ni 1-x M x )Si/Si(100) heterophase interface and may be responsible for the increased resistance of (Ni 1-x M x )Si to agglomeration at elevated temperatures. Direct evidence of Pt short-circuit diffusion via grain boundaries, Harrison regime-B, is found after silicidation to form (Ni 0.99 Pt 0.01 )Si. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The computational results are in agreement with the 3D atom probe measurements by Sonehara et al showing localized Pt distributions both at the silicide surface and at the silicide/Si interface [16]. They are also consistent with a computed reduction of the silicide/Si interfacial free energy by segregated Pt [15].…”
Section: Segregation Of Ptsupporting
confidence: 90%
See 1 more Smart Citation
“…The computational results are in agreement with the 3D atom probe measurements by Sonehara et al showing localized Pt distributions both at the silicide surface and at the silicide/Si interface [16]. They are also consistent with a computed reduction of the silicide/Si interfacial free energy by segregated Pt [15].…”
Section: Segregation Of Ptsupporting
confidence: 90%
“…An interesting experimental technique to address the spatial distribution of an element on the atomic level in a material is atom probe tomography. Local electrode (3D) atom probe measurements have indeed been carried out on Pt together with other dopants (Pd [15], As and B [16]) in Ni 1-x Pt x Si silicide films. It was found that Pt atoms segregates to the silicide/Si interface.…”
Section: Introductionmentioning
confidence: 99%
“…We briefly describe the atom probe process in the SI. Further descriptions of APT analysis and techniques are available in the literature. ,, For data collection, we use a LEAP4000XSi atom probe tomograph manufactured by CAMECA. , The sharpened tips are cryogenically cooled inside the LEAP instrument to a temperature of about 44 K. Atoms from the surface of the sharp tip are field-evaporated by applying a high voltage in the range 3–6 kV. Field-evaporation is assisted by ultraviolet laser pulses with 30 pJ pulse energy and a 250 kHz pulse repetition rate.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The combination of APT and TEM represents a powerful route to study the distributions of different species at an internal heterophase interface. 32 We have exploited these capabilities to study the mechanism of 1-D NB formation during volume-confined oxidation. We utilized Si as a marker atom to follow the structural evolution leading to the 1-D NB array, taking advantage of the difference in oxidation kinetics of Si vs Ge.…”
mentioning
confidence: 99%
“…ppm in concentration) is challenging using energy-dispersive X-ray spectroscopy (EDS) and/or electron energy-loss spectroscopy (EELS). The combination of APT and TEM represents a powerful route to study the distributions of different species at an internal heterophase interface . We have exploited these capabilities to study the mechanism of 1-D NB formation during volume-confined oxidation.…”
mentioning
confidence: 99%